The Whole Brain Creativity Model: Implications for Nursing Education and Practice - E Potgieter (AOSIS, 1999)
Recent nursing literature has repeatedly proclaimed the need for creativity in nursing. Effective nursing practice in the new millennium will require innovative and creative nurses who can adapt to change and have the courage to take risks in order to provide holistic, individualised, context-specific care. An analytical study of the literature revealed interesting information on the concept creativity and teaching for creativity. The aim of this article is to describe the Whole Brain Creativity Model and its implications for nursing education and practice.